Deep learning based diagnosis of Parkinson’s disease using convolutional neural network - Sivaranjini, S.; Sujatha, C. M. (Multimedia tools and applications, 2020)
Parkinson’s disease is the second most common degenerative disease caused by loss of dopamine producing neurons. The substantia nigra region is deprived of its neuronal functions causing striatal dopamine deficiency which remains as hallmark in Parkinson’s disease. Clinical diagnosis reveals a range of motor to non motor symptoms in these patients. Magnetic Resonance (MR) Imaging is able to capture the structural changes in the brain due to dopamine deficiency in Parkinson’s disease subjects. In this work, an attempt has been made to classify the MR images of healthy control and Parkinson’s disease subjects using deep learning neural network. The Convolutional Neural Network architecture AlexNet is used to refine the diagnosis of Parkinson’s disease. The MR images are trained by the transfer learned network and tested to give the accuracy measures. An accuracy of 88.9% is achieved with the proposed system. Deep learning models are able to help the clinicians in the diagnosis of Parkinson’s disease and yield an objective and better patient group classification in the near future.